ОПЫТ ИНТЕРПРЕТАЦИИ ДАННЫХ ПСИХОЛИНГВИСТИЧЕСКОГО ЭКСПЕРИМЕНТА (НА МАТЕРИАЛЕ АССОЦИАТИВНОГО ПОЛЯ КОНЦЕПТА РОДИНА) - Dżambajewa, Żanar (Przegląd Rusycystyczny, 2017)
INTERPRETACJA DANYCH EKSPERYMENTU PSYCHOLINGWISTYCZNEGO (NA MATERIALE POLA ASOCJACYJNEGO KONCEPTU OJCZYZNA) Streszczenie W artykule przedstawiono wyniki interpretacji danych eksperymentu psycholingwistycznego na materiale pola asocjacyjnego konceptu ojczyzna w świadomości językowej społeczności słowiańskich, zamieszkujących na terytorium Republiki Kazachstanu. Eksperyment potwierdził, że czynnik wartościujący jest jednym z istotnych parametrów konceptu ojczyzna i stanowi jego nieodłączną cześć. INTERPRETATION OF DATA OBTAINED IN A PSYCHOLINGUISTIC EXPERIMENT (ON THE BASIS OF THE MATERIAL RELATED TO THE ASSOCIATE FIELD OF THE CONCEPT OF THE HOMELAND) Summary The article presents interpretation of results obtained in a psycholinguistic experiment on the of the material related to the associate field of the concept of the homeland in the language consciousness of the Slavic societies living in the territory of the Republic of Kazakhstan. The experiment proved that the value factor is one of the crucial features of the concept of the homeland and constitutes its essential part.